Peningkatan Nilai Tambah Limbah Kotoran Kambing Menjadi Pupuk Kotoran Hewan di BPP Genteng Kabupaten Banyuwangi - Indraloka, Aldy Bahaduri; Meidayanti, Karina; Ratri, Indira Nuansa (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2023)
Goat waste product of livestock waste would given negative impact if it was not used. The purpose of this communal service activity were to increase the added value of goat waste product at BPP Genteng, Banyuwangi which has not been utilized before. This communal service is carried out by training the use of animal waste product by using chopping machines and training in the manufacture of animal manure fertilizers. The results of the service activities show that the community in BPP Genteng have been able to make manure fertilizer using a grinding machine for time and energy efficiency in the fertilizer production process. The community service program was carried out well where this activity received a positive response from BPP Genteng, breeders and farmer groups in participating in socialization activities, training on fertilizer production and socialization of application and maintenance of the machines. These three activities aimed to increase the added value of goat manure waste in BPP Genteng.